Use of a Multivector Mandibular Distractor for Treatment of Pediatric Proximal Interphalangeal Joint Pilon Fractures: A Case-Based Review - Pedreira, Rachel; Cho, Brian H.; Geer, Angela; DeJesus, Ramon A. (Journal of Hand and Microsurgery, 2018)
Background The difficulties in surgical treatment of pilon fractures of the finger include fragment reconstitution and posthealing stiffness. In adults, external fixation with traction and early active range of motion (AROM)/passive range of motion (PROM) during healing is considered necessary for avoiding joint stiffness and attaining realignment. The authors present a unique approach to pediatric pilon fractures that uses open reduction and multivector external fixation with delayed AROM/PROM. Initial immobilization and significant traction allowed for joint realignment and prevented noncompliance with staged distraction. The authors believe this immobilization leads to a superior outcome because, unlike adults, children tend to avoid stiffness and a larger distraction force allowed for sufficient joint realignment to regain range of motion (ROM).Methods A right-handed 13-year-old boy sustained a right ring finger fracture and presented 12 days later. Radiographs revealed a comminuted Salter-Harris 4 fracture of the middle phalanx. The patient underwent open reduction and placement of multivector external fixation using a pediatric mandibular distractor/fixator. Significant traction was applied to distract the finger to length.Results Hardware was removed 6 weeks postoperatively and AROM was initiated after splinting. The patient started PROM 8 weeks postoperatively. Strengthening was initiated 2 weeks later. ROM improved and rehabilitation was continued. The patient exhibited nearly equal grip strength 12 weeks postoperatively. At 14 months follow-up, radiographs showed complete healing and joint realignment. There was no deformity or pain and finger length was restored.Conclusion Management of pediatric pilon fractures is rarely described and presents unique considerations. Early-stage traction and immobilization using a multivector mandibular fixator/distractor is suitable in a child because noncompliance is avoided and there is a decreased risk for stiffness. Combining early immobilization with subsequent-staged AROM, PROM, and strengthening resulted in no loss of ROM and maintained articular symmetry.
Keywords: proximal interphalangeal joint; fracture; pilon fracture; pediatric hand; external fixation; mandibular fixator